How the corona pandemic affects the global fight against tuberculosis and how to react - Ulrichs, Timo (Frontiers in Cellular and Infection Microbiology, 2023)
The emergence of the acute pandemic by SARS-CoV-2 is a setback for the fight against chronic pandemics like tuberculosis (TB), malaria, and HIV/AIDS. In fact, after more than a decade of decreasing fatality numbers, 2020 saw a re-increase in the number of people dying from TB. After COVID-19, TB was the infectious disease with the second-highest fatality rate caused by a single pathogen, with 1.6 million deaths in 2021. It is expected by the WHO that the pandemic years to come and even after the pandemic will continue this trend. More efforts are needed to support TB control structures as an integral part of the strengthening measures of the general health care system.